The Multangular-Pyramid Concave Friction System (MPCFS) for seismic isolation: A preliminary numerical study. (1st April 2018) - Xiong, Wei; Zhang, Shan-Jun; Jiang, Li-Zhong; Li, Yao-Zhuang
Highlights: The Multangular-Pyramid Concave Friction System (MPCFS) for seismic isolation is introduced. The vertical load sustaining capacity is improved of the MPCFS than CFS. Frequency-sweeping analysis verifies the shun-resonance ability of the MPCFS. The numerical simulation for fixed-base, MPCFS, CSS, is performed. Numerical results testify the noted virtues of the MPCFS. Abstract: The Multangular Pyramid Concave Friction System (MPCFS) is introduced in this study. Different from the conventional Curved Surface Slider (CSS), the concavity of the MPCFS is designed as a multangular (mostly triangular or rectangular) pyramid, and the slider is removed from the isolator. While maintaining the virtues of the CFS, the MPCFS can provide greater vertical sustaining capacity with a more stable friction force. When combined with a cross uplift restraint, the MPCFS offers numerous virtues such as increased uplift stability, a greater initial yielding force, and resonance-dodge ability during near-fault earthquakes (variable frequency). Frequency-sweeping and acceleration time-history numerical investigations are conducted on a four-storey building model using the MPCFS. The revised State-Space Method (SSM) is expanded from two-degrees-of-freedom to multi-degrees-of-freedom as to accommodate more complex analysis such as dynamic analysis of high-rise, multi-storey structure installed with MPCFS. The simulation result verifies the merits of the MPCFS, indicating that the MPCFS, viewed as a beneficial complement to the existing well-established isolation techniques, may be a promising tool for the seismic isolation of high-rise, and super high-rise buildings in near-fault earthquake prone zones.